Emerging proteomic biomarkers of X-linked muscular dystrophy. (3rd August 2019) - Dowling, Paul; Murphy, Sandra; Zweyer, Margit; Raucamp, Maren; Swandulla, Dieter; Ohlendieck, Kay
ABSTRACT: Introduction : Progressive skeletal muscle wasting is the manifesting symptom of Duchenne muscular dystrophy, an X-linked inherited disorder triggered by primary abnormalities in the DMD gene. The almost complete loss of dystrophin isoform Dp427 causes a multi-system pathology that features in addition to skeletal muscle weakness also late-onset cardio-respiratory deficiencies, impaired metabolism and abnormalities in the central nervous system. Areas covered : This review focuses on the mass spectrometry-based proteomic characterization of X-linked muscular dystrophy with special emphasis on the identification of novel biomarker candidates in skeletal muscle tissues, as well as non-muscle tissues and various biofluids. Individual sections focus on molecular and cellular aspects of the pathogenic changes in dystrophinopathy, proteomic workflows used in biomarker research, the proteomics of the dystrophin-glycoprotein complex and the potential usefulness of newly identified protein markers involved in fibre degeneration, fibrosis and inflammation. Expert opinion : The systematic application of large-scale proteomic surveys has identified a distinct cohort of both tissue- and biofluid-associated protein species with considerable potential for improving diagnostic, prognostic and therapy-monitoring procedures. Novel proteomic markers include components involved in fibre contraction, cellular signalling, ion homeostasis, cellular stress response, energy metabolism and the immune response, as well as maintenance of the cytoskeletal and extracellular matrix.